2017
DOI: 10.2118/183650-pa
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Bayesian Computation for Probabilistic Decline-Curve Analysis in Unconventional Reservoirs

Abstract: Summary In this work, we developed a methodology that integrates decline-curve-analysis (DCA) models with an approximate Bayesian probabilistic method that is based on rejection sampling to quantify the uncertainty associated with DCA models. This methodology does not require the estimation of the likelihood, which simplifies the Bayesian inference greatly. In approximate Bayesian computation (ABC) with rejection sampling, the posterior distribution is approximated by substituting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Several authors have suggested alternatives to the traditional DCA. These are, e.g., the Power Law Exponential Decline [11], the Stretched Exponential Decline [12,13], the Logistic Growth Model [14], the Bayesian probabilistic DCA [15,16], and the Extended Exponential DCA [17]. Empirical models are simple, but they also are mere curve fits, whose parameters have little physical meaning and cannot be generalized.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have suggested alternatives to the traditional DCA. These are, e.g., the Power Law Exponential Decline [11], the Stretched Exponential Decline [12,13], the Logistic Growth Model [14], the Bayesian probabilistic DCA [15,16], and the Extended Exponential DCA [17]. Empirical models are simple, but they also are mere curve fits, whose parameters have little physical meaning and cannot be generalized.…”
Section: Introductionmentioning
confidence: 99%
“…An example of a probabilistic method used mostly is the Bayesian theorem or computation. [54][55][56][57][58] Patzek et al (2013) proposed the use of a simple scaling theory and growth model for forecasting the production of hydraulic fracture wells completed in gas reservoirs. 59,60 Recently, the applications of supervised ML, deep learning (DL), and articial intelligence (AI) have been implemented.…”
Section: Papermentioning
confidence: 99%
“…To obtain the best predictive model, production data from 10,000 wells were transformed into DCA space. DCA best fit curves were usually computed with the least-squares regression [34]. Thus, leastsquares regression was programmed to estimate the three determining parameters of the Arps decline model from the 10,000 synthetic cumulative production profiles generated by the represented reservoir simulation.…”
Section: Decline Curve Analysis Regressionmentioning
confidence: 99%